ANALISA FAKTOR - FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT YANG DILAKUKAN OLEH BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA (Studi Kasus pada BPK RI Perwakilan Provinsi Kepulauan Bangka Belitung) - Arista Rizky Indriyanto; Nasi kin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this research is to examines the influence of auditor’s educational background, auditor’s experience, auditor’s training hours, audit structure, role conflict, and role ambiguity on BPK RI Perwakilan Provinsi Kepulauan Bangka Belitung’s audit quality. The number of respondents in this research are 34 auditors. This research is using a cencus method as the method of determining the sample, because the number of the population is under 100 respondent. Data processing methods that used in this research is multiple regression analysis.The result of this research shows auditor’s educational background, auditor’sexperience, auditor’s training hours, audit structure, role conflict, and roleambiguity simultaneously and significantly influence BPK RI Perwakilan ProvinsiKepulauan Bangka Belitung’s audit quality. Partially, only role conflict and roleambiguity significantly influence the audit quality. Auditor’s educationalbackground, auditor’s experience, auditor’s training hours, and audit structureunsignificantly influence the audit quality.Keywords : auditor’s educational background, auditor’s experience, auditor’straining hours, audit structure, role conflict, role ambiguity, audit quality, bpk ri.